(untitled) (Al-Qamar, 2021)
Imam Ahmed Raza Khan is not only an Islamic scholar but also a great Muslim Scientist of his Century. Allah Granted him with great heights of knowledge. He wrote many books on different Topics such as Quran, Sunnah Fiqh and Modern Science. Imam Ahmed Raza Khan is a e great mathematician also. He wrote about fifty books on this topic. He used to solve the most difficult mathematical problems. This article discusses his contributions in the field of mathematics and highlights his expertise in Aljabra, geometry, calculus, logarithms, arithmetic and other branches of mathematics.